Epidemiology of Ectoparasites (Ticks, Lice, and Mites) in the Livestock of Pakistan: A Review - Muhammad, Ali; Bashir, Rida; Mahmood, Majid; Afzal, Muhammad Sohail; Simsek, Sami; Awan, Usman Ayub; Khan, Mobushir Riaz; Ahmed, Haroon; Cao, Jianping (Frontiers in Veterinary Science, 2021)
Ectoparasites, including lice, ticks, and mites, inhabit the host skin and depend on their host for sustenance, maturation, and multiplication. Among these, ticks are more prevalent in various regions of Pakistan because of favorable climatic conditions, lack of livestock keepers’ awareness of the ectoparasite infestation rate, insufficient veterinary services, and inadequate control measures. Ectoparasitic infestation is a primary threat to cost-effective livestock production by damaging skin and transmitting multiple diseases between animals. This review aimed to determine the infestation rates of various ectoparasites in cattle, buffaloes, sheep, goats, camels, and equids and ascertain the prevalence and epidemiology of ectoparasites in different regions of Pakistan. This review could be useful in devising prevention and control strategies and identifying the risk factors associated with ectoparasites to enhance animal productivity. It provides directions for veterinary schools, researchers, and organizations aiming to collaborate with neighboring countries to eradicate these parasites. Future studies could support working veterinarians and administrators and contribute to human well-being.